2011
DOI: 10.1021/la200052t
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Selective Detection of Silver(I) Ion in Aqueous Solution Using Carbon Nanoparticles as a Cheap, Effective Fluorescent Sensing Platform

Abstract: In this Letter, we demonstrate the first use of carbon nanoparticles (CNPs) obtained from carbon soot by lighting a candle as a cheap, effective fluorescent sensing platform for Ag(+) detection with a detection limit as low as 500 pM and high selectivity. We further demonstrate its practical application to detect Ag(+) in a real sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 31 publications
1
80
0
Order By: Relevance
“…A quenching effect on CQD fluorescence has been observed for CQDs synthesized from lactose and then functionalized with mercaptosuccinic acid [27] as a result of the thiolAg interaction. In the other hand, other authors [28][29][30] reported a second mechanism of Ag + detection based on an enhancement on the carbon-based nanodots fluorescence due to the reduction of Ag + to Ag 0 . Furthermore, such mechanism makes it feasible to synthesize silver nanoparticles [31][32].…”
Section: Introductionmentioning
confidence: 99%
“…A quenching effect on CQD fluorescence has been observed for CQDs synthesized from lactose and then functionalized with mercaptosuccinic acid [27] as a result of the thiolAg interaction. In the other hand, other authors [28][29][30] reported a second mechanism of Ag + detection based on an enhancement on the carbon-based nanodots fluorescence due to the reduction of Ag + to Ag 0 . Furthermore, such mechanism makes it feasible to synthesize silver nanoparticles [31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high toxicity and the ability to accumulate in the body, Ag + ions are particularly dangerous to aquatic organisms [3,4]. Thus, the detection of Ag + is of particular importance [5][6][7][8][9][10][11][12]. A few approaches for the detection of Ag + have been developed, including inductively coupled plasma-mass spectroscopy (ICP-MS) [13], atomic absorption spectroscopy [14], fluorescence spectroscopy [15], and ion-selective electrodes (ISE) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between Ag + and cytosine-cytosine (C-C) mismatches has been extensively studied and numerous oligonucleotide-based fluorescent Ag + sensors have been developed [9,[18][19][20][21][22][23]. Ono et al reported the selective interaction of Ag + with C-C mismatches, and developed a fluorescent Ag + sensor for detecting aqueous Ag + ions using C-rich silver-specific oligonucleotides (SSO) doubly labeled with a fluorophore and a quencher [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li et al reported a graphene-based fluorescent DNA sensor for silver(I) ions detection. 19 A fluorescein (FAM) labeled C-rich single strand DNA (ssDNA) was applied in this study. In the absence of Ag + , graphene oxide (GO) can selectively absorb and quench the fluorescence of ssDNA by the formation of stable GO-DNA complexes.…”
Section: Introductionmentioning
confidence: 99%